FOOD SALES SYSTEM ADMINISTRATION ON LIVESTOCK CV. PRIMA CIKUPA USING VB.6.0 - Desak Nyoman Mulyani; Aqwam Rosadi Kardian, Skom, MM (Jurnal Sistem Informasi, 2004)
Part marketing, particularly the sales division is a very important part for the declineof a company forward. Because of where the goods or services a company will bemarketed or sold to generate income for the companies themselves. By analyzing theexisting sales process and then sets out into the new system, with the goal of keepingthe sales process is expected to be increased. Explanation can be seen from the DataFlow Diagram of Diagram Context and Zero, Entity Relationship Diagrams andNormalization, as well as components such as customer data management, goods andtransactions. By limiting the problems in the manufacture Formats orders, invoices orreceipts and sales reports sederhanan hence made a program that uses MicrosoftVisual Basic or for processing the above data.